Frozen-thawed double cleavage-stage or frozen-thawed single day 6 blastocyst stage embryo transfer: which is preferable for patients younger than 35 without day 5 blastocyst formation? - Liu, Yan; Wang, Taojun; Dai, Shanjun; Shi, Hao; Sun, Yingpu (Frontiers in Endocrinology, 2025)
BackgroundTo compare the clinical outcomes between frozen-thawed cleavage embryo transfer and frozen-thawed day 6 blastocyst transfer in patients younger than 35 using the freeze-all strategy without day 5 blastocyst formation.MethodsThis was a retrospective observational analysis performed between January 2018 and December 2022 at the Reproductive and Genetic Specialist Hospital of the First Affiliated Hospital of Zhengzhou University. A total of 576 patients younger than 35 who used the “freeze-all strategy” but produced no day 5 blastocysts were recruited. The patients were divided into 3 groups according to the number and stage of the transferred embryos: double cleavage-stage embryos (Group A), single good-quality day 6 blastocysts (Group B) and single inferior-quality day 6 blastocysts (Group C),and several pregnancy outcomes were measured.ResultsGroups A and B exhibited significantly higher chemical (73.7%, 67.0% versus 51.9%) and clinical pregnancy rates (69.0%, 59.4% versus 44.2%) than Group C. The implantation rate was significantly higher in Group B than in Groups A and C (59.4% versus 45.7%, 43.5%). The live birth rate was significantly higher in Group A than in Group C (59.2% versus 48.1%). The multiple pregnancy rate was significantly higher in Group A than in Groups B and C (34.4% versus 1.6%, 1.5%). The early miscarriage rate was significantly higher in Group C than in Group A and Group B (23.5% versus 8.7%, 12.7%). Premature delivery rates, late miscarriage rates and ectopic pregnancy rates were comparable across groups.ConclusionsA single good quality day 6 blastocyst transfer was the preferable strategy for the freeze-all strategy patients who younger than 35 and without day 5 blastocyst formation.